S-CDK-regulated bipartite interaction of Mcm10 with MCM is essential for DNA replication - Wang, Xueting; Liu, Lu; Chen, Mengke; Quan, Yun; Zhang, Jiaxin; Lou, Huiqiang; Xia, Yisui; Chen, Hongxiang; Hou, Wenya (Frontiers in Cell and Developmental Biology, 2024)
Mcm10 plays an essential role in activation of replicative helicase CMG through the cell-cycleregulated interaction with the prototype MCM double hexamer in Saccharomyces cerevisiae. In this study, we reported that Mcm10 is phosphorylated by S-CDKs at S66, which enhances Mcm10-MCM association during S phase. S66A single mutation or even deletion of whole N-terminus (a.a. 1-128) only causes mild growth defects. Nevertheless, S66 becomes indispensable in the absence of Mcm10 C-terminus ((a.a. 463-571), the major MCM-binding domain. By using a two-degron strategy to deplete Mcm10 efficiently, we show that mcm10-S66AΔC has a severe defect in proceeding into S phase. Strikingly, both lethality and S phase deficiency can be rescued by artificially tethering mcm10-S66AΔC with MCM. These findings illustrate how Mcm10-MCM association is regulated as a crucial event in DNA replication initiation.